Root system-rhizosphere soil-bulk soil interactions in different Chinese fir clones based on fungi community diversity change - Cao, Yue; Li, Nana; Lin, Jingquan; Zhang, Yun; Ma, Xiangqing; Wu, Pengfei (Frontiers in Ecology and Evolution, 2022)
The diversity of the rhizosphere arbuscular mycorrhizal fungi (AMF) community is a crucial factor affecting root-soil interaction. They can absorb carbohydrates from the host body and return the nutrient elements from the soil to the host. Using 15 Chinese fir (Cunninghamia lanceolata Lamb. Hook.) clones, the AMF richness, abundance and community structure in "Root system- Rhizosphere soil- Bulk soil" were obtained by Real-time quantitative PCR (qPCR) and Illumina Miseq sequencing techniques. The results showed that under the same Chinese fir clone, the total amount of AMF was in the order of rhizosphere soil > root system > bulk soil. The species diversity and uniqueness of AMF were in the order of root system > rhizosphere soil > bulk soil. There was a significant correlation between soil-available phosphorus and AMF diversity and its dominant genera and species. Regarding AMF abundance, Chinese fir clone S18 is the highest, followed by clones Y061 and P17. There was a significant difference in AMF richness among different clones, and Glomus was the dominant genus of AMF. The AMF species diversity of P17 and S2 in roots and rhizosphere soil was high, indicating a good symbiosis between roots and the AMF community. However, the AMF diversity of clones P11 and P41 was low, and the variation of AMF community composition in the group was small. The root-soil interaction caused the AMF community to gather in the rhizosphere but had less symbiosis present with roots. Still, the AMF diversity of the rhizosphere soil of both clones was high. There was a significant correlation between the soil-available phosphorus content and the species diversity of AMF and its dominant genera and species. In conclusion, Clone P17 has high AMF richness and abundance and forms a good symbiosis with AMF, which could be a nutrient-efficient clone of Chinese fir.